2013
DOI: 10.1007/s00590-013-1195-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of proximal femoral nail antirotation (PFNA) with AO dynamic condylar screws (DCS) for the treatment for unstable peritrochanteric femoral fractures

Abstract: PurposeThe aim of this study was to compare the results of intramedullary fixation with those of plate-screw fixation for peritrochanteric femoral fracture patients older than 60 years old.MethodsThis article reports on a retrospective review of patients who had peritrochanteric femoral fractures and were treated with a 95° fixed-angle screw plate (DCS) or an intramedullary nailing system (PFNA). Patients with 79 fractures were enrolled in the study; 47 of them were treated with the PFNA system and 37 with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 28 publications
0
32
1
Order By: Relevance
“…14 They found that the mean salvati-wilson hip score was 31 in the PFNA group and 26 in the DCS group. They had good results in 73.9% of the patients in the PFNA group and 70% in the DCS group.…”
Section: Discussionmentioning
confidence: 99%
“…14 They found that the mean salvati-wilson hip score was 31 in the PFNA group and 26 in the DCS group. They had good results in 73.9% of the patients in the PFNA group and 70% in the DCS group.…”
Section: Discussionmentioning
confidence: 99%
“…They had no complications like cut out or breakage of the implant. They concluded that long proximal femoral nail or long gamma nail is a reliable implant in treatment of subtrochanteric fractures Sahin EK et al did a comparison of proximal femoral nail antirotation with dynamic condylar screw in the elderly in the treatment of pertrochanteric fracture of the femur [17]. They found that the mean salvati-wilson hip score was 31 in the PFNA group and 26 in the DCS group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that an IM nail provides high union rates with low major complication rates, it has been associated with lateral trochanteric wall impingement that causes lateral trochanteric wall fracture during insertion, particularly for Asian patients with a narrow and short proximal femoral anatomy [17, 19, 21, 2628]. PFNA II has been improved for the Asian patient with a flattened lateral surface, and the decreased mediolateral nail angle tends to reduce the risk of impingement with the lateral trochanteric wall [6, 19, 29].…”
Section: Discussionmentioning
confidence: 99%